Scope for sustainable development of small holder farmers in the palm oil supply chain: A systematic literature review and thematic scientific mapping - Ahmed Zainul Abideen; Veera Pandiyan Kaliani Sundram; Shahryar Sorooshian (Logistics, 2023)
Background: The expansion of oil palm agriculture across the nations, especially in countries such as Malaysia and Indonesia, is growing at exacerbated levels. However, there is still a lack of awareness of the environmental, social, and economic challenges among the sector, ranging from the combination of ecological, economic, and ecosystem sustainability to the livelihoods of plantation workers and small holder communities. Small holders struggle to attain the primary standards on market governance, debt-free livelihood enhancements, certification norms, proper land rights and usage, outsourcing quality seeds, harvesting technologies, labor usage, etc. Method: There is a need to systematize the existing literature toward one that addresses the most fundamental and urgent questions that govern the palm oil small holder sustainability in the palm oil supply chain. The objective of this article is two-fold. One approach was to undertake an integrated systematic review and thematic scientific mapping of the last 10 years of research effort (2009-2020) on the specified research agenda, using data from the Web of Science (WoS) core collection database. Another objective was to gain insights and research direction. Results: The defined gaps and insights from the study helped to form the basis for developing a conceptual framework for achieving the sustainability and livelihood of small holders in the palm oil sector. Conclusions: There is a stringent need to focus on the sustainability factors of small holders in the palm oil upstream logistics to address and improve the overall efficiency of the supply chain.
Keywords: 650; agricultural logistics; palm oil sector; palm oil supply chain; small holder farmers; sustainability